Simulasi Rumah Pintar Berbasis IOT Menggunakan Aplikasi Cisco Paket Tracer - Mickhel; Anthony; Thionuartha, Kevin; Pernando, Yonky (Fakultas Komputer - Universitas Universal, 2025)
The development of Internet of Things (IoT) technology has driven the creation of smart home systems, which enhance comfort, security, and energy efficiency for occupants. This study aims to simulate an IoT-based smart home system using Cisco Packet Tracer as a visualization and network testing tool. In this simulation, various smart devices—such as automated lights, temperature sensors, fans, and digital doors—were configured and integrated using IoT communication protocols. The simulation results demonstrate that Cisco Packet Tracer can be effectively used to model interactions between devices in a smart home network and test automated responses based on input from installed sensors. This simulation is expected to serve as a foundation for developing more complex smart home systems and as a learning medium for understanding basic IoT concepts in home automation